POTENSI BUDAYA DI DESA WISATA PENGADANGAN KABUPATEN LOMBOK TIMUR SEBAGAI DAYA TARIK WISATA - Nila Apriliana Utami; I Ketut Bagiastra; I Made Suyasa (Journal Of Responsible Tourism, 2023)
This study discusses the Potential of Cultural Tourism in Pengadangan Village, East Lombok Regency as a Cultural Tourism Attraction in East Lombok Regency as a Turist Attraction. This research was conducted in order to answer the problems in question, namely to find out the cultural potential possessed and know how tonpreserve the Pengadangan Tourism Village as a cultural tourism attraction as a tourist attraction. This writing is presented in a qualitative descriptive manner to obtain an overview of the cultural potential and efforts to develop the Pengadangan Tourism Village. The techniques used in data collection are observation techniques, interview techniques and documentation techniques. The results of this study indicate that Pengadangan Tourism Village has various cultural potentials in the form of traditions and customs (Ngalu Ujan, Betetulak, Njeleng Oil 1000 Hajat and Nggaro Gareng) handicrafts (Prabot Preaq and woven cloth) traditional foods (sambal raden, rusu lindung, bebetok, later batih) musical arts (slober, rerantok, gamelan beleq and cungklik) and traditional clothing (lambung and pegon). The conclusion that can be drawn regarding the efforts to develop the Pengadangan Tourism Village as a cultural tourism attraction is that the development of cultural potential in the Pengadangan village is needed to maintain and preserve the cultural heritage assets owned. Pengadangan Village still has room to develop and compete in the tourism world of East Lombok Regency.